Esej o japońskich menedżerach i ich gospodarce - Saykiewicz, Andrzej (Essay on Japanese managers and economy, 2006)
After having spent over 30 years in Japan, working in senior positions for major Japanese companies and leading numerous international trade and investment projects, Mr. Saykiewicz shares with us his knowledge and analysis of Japan’s economy, the roots of its success, and the reasons why Japan is not understood in the West. This cognitive gap influences Western analysis of economic developments in Japan, as well as conducting business with Japanese partners. Mr. Saykiewicz explains the Japanese managerial culture and techniques, the different types of managers, and gives us a glimpse into differences in communication between Japanese managers and their “western” counterparts. Bearing these differences in mind should help Western business community in their dealings with Japan.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 129-138